VISI PROFETIK HAJI: STRATEGI KEBUDAYAAN DALAM TRANSFORMASI SOSIAL - Suwito Suwito (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This article describe and analyze the prophetic vision of hajj in AliSyari’ati perspective. The analysis applies social approach as stated byKuntowijoyo as prophetic social science. There are three aims on propheticsocial, humanism, liberation and transcendence. This article showsthat hajj does not only make people closer to the God but also teach themto be more sensitive to the environment. There are three essential meanings,humanism, liberalism and transcendence.